Sex differences in stroke therapies. Issue 1 (2nd January 2017) - Sohrabji, Farida; Park, Min Jung; Mahnke, Amanda H.
Abstract : Stroke is the fifth leading cause of death and acquired disability in aged populations. Women are disproportionally affected by stroke, having a higher incidence and worse outcomes than men. Numerous preclinical studies have discovered novel therapies for the treatment of stroke, but almost all of these have been shown to be unsuccessful in clinical trials. Despite known sex differences in occurrence and severity of stroke, few preclinical or clinical therapeutics take into account possible sex differences in treatment. Reanalysis of data from studies of tissue plasminogen activator (tPA), the only currently FDA‐approved stroke therapy, has shown that tPA improves stroke outcomes for both sexes and also shows sexual dimorphism by more robust improvement in stroke outcome in females. Experimental evidence supports the inclusion of sex as a variable in the study of a number of novel stroke drugs and therapies, including preclinical studies of anti‐inflammatory drugs (minocycline), stimulators of cell survival (insulin‐like growth factor‐1), and inhibitors of cell death pathways (pharmacological inhibition of poly[ADP‐ribose] polymerase‐1, nitric oxide production, and caspase activation) as well as in current clinical trials of stem cell therapy and cortical stimulation. Overall, study design and analysis in clinical trials as well as in preclinical studies must include both sexes equally, consider possible sex differences in the analyses, and report the differences/similarities in more systematic/structured ways to allow promising therapies for both sexes and increase stroke recovery. © 2016 Wiley Periodicals, Inc.